Respuestas
Respuesta dada por:
1
x² + 2x - 4x - 8 = 0
x² - 2x - 8 = 0
![x = \frac{2 +- \sqrt{4 + 32} }{2} x = \frac{2 +- \sqrt{4 + 32} }{2}](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B2+%2B-++%5Csqrt%7B4+%2B+32%7D+%7D%7B2%7D+)
![x = \frac{2 +- \sqrt{36} }{2} x = \frac{2 +- \sqrt{36} }{2}](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B2+%2B-++%5Csqrt%7B36%7D+%7D%7B2%7D+)
x₁ = (2 + 6) : 2 = 4
x₂ = (2 - 6) : 2 = -2
x² - 2x - 8 = 0
x₁ = (2 + 6) : 2 = 4
x₂ = (2 - 6) : 2 = -2
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años